Warning about the harms of tobacco use in 22 countries: findings from a cross-sectional household survey. Issue 4 (7th May 2015) - Chiosi, John J; Andes, Linda; Asma, Samira; Palipudi, Krishna; McAfee, Tim; ,
Abstract : Background: Knowledge about the harms of tobacco use deters initiation and is associated with cessation. Most studies on this knowledge in the general population have been in high-income countries, but the tobacco use burden is increasing in low-income and middle-income countries. We sought to estimate levels of knowledge about tobacco-related diseases in 22 countries and determine the factors associated with differences in knowledge. Methods: We used data from the Global Adult Tobacco Survey (GATS), a nationally representative survey of persons aged ≥15 years. GATSs were conducted from 2008 to 2013 in 22 low-income and middle-income countries. Information was gathered on tobacco-related knowledge and noticing of antismoking mass media messages and health warning labels on cigarette packages. We constructed a four-point knowledge scale and performed multivariate regression analyses. Results: Median country values for the proportion of adults who believed smoking causes a specific illness were 95.9% for lung cancer, 82.5% for heart attack and 74.0% for stroke. Knowledge scores ranged from 2.1 to 3.8. In multivariate regressions, adults scored significantly higher on the knowledge scale if they noticed antismoking media messages (22 countries) or health warning labels (17 countries). Significantly higher knowledge scores occurred in all 9 countries with pictorial health warning labels compared with only 8 out of 13 countries with text-only warning labels. Conclusions: Antismoking media messages appear effective for warning the public about the harms from tobacco use in all 22 countries, while warning labels are effective in the majority of these countries. Our findings suggest opportunities to motivate smoking cessation globally.